Evangelism and apostasy : the evolution and impact of evangelicals in modern Mexico - Bowen, Kurt, 1946- (McGill-Queen's studies in the history of religion, 1996)
In this sociological assessment of the Evangelical movement in Mexico, Kurt Bowen highlights the demographic, social, and political character of the movement in the 1980s and 1990s. He pays particular attention to conversion processes, commitment mechanisms, schisms, and distinctive beliefs. Bowen also considers the controversial issues of religious persecution and American missionary influence. Bowen reveals that Evangelicalism's appeal is so pervasive in Mexico that if Evangelical converts all remained faithful it could become Mexico's dominant religion by 2006. This projection, however, is improbable due to high drop-out rates and Bowen argues that Evangelical apostasy is rooted in the most basic beliefs and practices of its followers.